Quantifying nutrient loss across particle size fractions in eroded tropical soils using 239+240Pu fallout radionuclides - Job Isaboke; Olivier S. Humphrey; Ruth Njoroge; Odipo Osano; Michael J. Watts (Soil and Tillage Research, 2026)

Sediment and soil source apportionment using geochemical fingerprinting techniques in the Winam Gulf, Lake Victoria - Olivier S. Humphrey; Job Isaboke; Odipo Osano; Christopher Mulanda Aura; William H. Blake; Michael J. Watts (CATENA, 2025)

Plutonium isotopes can be used to model soil erosion in Kenya - Sophia Dowell; Olivier Humphrey; Job Isaboke; Thomas Barlow; William Blake; Odipo Osano; Michael Watts (Environmental Geochemistry and Health, 2024)
Climate change poses an immediate threat to tropical soils with changes in rainfall patterns resulting in accelerated land degradation processes. To ensure the future sustainability of arable land, it is essential to improve our understanding of the factors that influence soil erosion processes. This work aimed to evaluate patterns of soil erosion using the activity of plutonium isotopes (Pu) at sites with different land use and clearance scale in the Winam Gulf catchment of Lake Victoria in Kenya. Erosion rates were modelled at potential erosive sites using the MODERN model to understand small-scale erosion processes and the effect of different management practices. The lowest soil redistribution rates for arable land were 0.10 Mg ha −1 yr −1 showing overall deposition, resulting from community-led bottom-up mitigation practices. In contrast erosion rates of 8.93 Mg ha −1 yr −1 were found in areas where steep terraces have been formed. This demonstrates the significance of community-led participation in effectively managing land degradation processes. Another key factor identified in the acceleration of soil erosion rates was the clearance of land with an increased rate of erosion over three years reported (0.45 to 0.82 Mg ha −1 yr −1 ) underlining the importance vegetation cover plays in limiting soil erosion processes. This novel application of fallout plutonium as a tracer, highlights its potential to inform the understanding of how soil erosion processes respond to land management, which will better support implementation of effective mitigation strategies. Graphical abstract Modelling of soil erosion and deposition patterns using the MODERN model to calculate the depth of soil loss/gain.

Suitability of 210Pbex, 137Cs and 239+240Pu as soil erosion tracers in western Kenya - Sophia M. Dowell; Olivier S. Humphrey; Charles J.B. Gowing; Thomas S. Barlow; Simon R. Chenery; Job Isaboke; William H. Blake; Odipo Osano; Michael J. Watts (Journal of Environmental Radioactivity, 2024)